1991
DOI: 10.2165/00003088-199121040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Anxiolytics and Hypnotics in the Elderly

Abstract: Part I of this article, which appeared in the previous issue of the Journal, discussed the scope of and scientific basis for special pharmacokinetic studies of anxiolytic and hypnotic drugs in the elderly, and examined the methodology and results of such studies and the prediction of pharmacokinetic changes. In Part II the authors continue their review, focusing on age-related pharmacodynamic changes in the effects of these drugs, the attempts to correlate pharmacokinetic with pharmacodynamic findings, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 131 publications
2
37
1
1
Order By: Relevance
“…The probability of experiencing postoperative pain was reduced by 3% for each additional year of life. 13,14 Furthermore, the age-related reduction of plasma protein concentration might increase the percentage of unbound active drug concentration. 3,8,9 It was suggested that older patients may be more pain tolerant owing to a loss of pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of experiencing postoperative pain was reduced by 3% for each additional year of life. 13,14 Furthermore, the age-related reduction of plasma protein concentration might increase the percentage of unbound active drug concentration. 3,8,9 It was suggested that older patients may be more pain tolerant owing to a loss of pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic drug-metabolizing enzymes, including cytochrome (CYP) P450 enzymes (with CYP3A4 primarily responsible for metabolizing fentanyl in humans) (5), are reduced in quantity and function in older patients (6), who make up the majority of ICU patients. Moreover, critical illness often results in failure of organs that affect pharmacokinetics, e.g., the liver, kidney, and heart.…”
mentioning
confidence: 99%
“…Rekonstruktive Therapie bei eingeschränkten physischen und psychischen Ressourcen gnitive Leistung und somit die zahnärztliche Behandlungs-und Betreuungsfähigkeit gerade älterer Patienten massiv zu reduzieren vermögen [14,15]. Dies trifft u. a. auf die sog.…”
Section: Der Alternde Patient Mit Seinen Besonderen Bedürfnissenunclassified